Epidemiology of breast cancer mortality in Brazil between 2009 and 2019 and the influence of socioeconomic and demographic aspects (Research, Society and Development, 2021)
This study aimed to review the Brazilian epidemiology of female breast cancer mortality in the period between 2009 and 2019, presenting the main characteristics of the disease profile in the country and analyzing the influence of socioeconomic and demographic variables on fatal records. This is an ecological and descriptive study, guided by data obtained through the electronic platform of the Mortality Information System (SIM). The number of deaths was progressive over the range evaluated and the average of deaths in these years was equal to 15,095, with a percentage of 98.85% in female mortality, while in men, the figure was found. was only 1.15%. As for the distribution of female deaths among Brazilian macro-regions, the Southeast represented 51.01% of the 164,153 verified throughout the country. The population that accounted for most of the deaths was composed of women aged between 50 and 59 years, white (59.66%) and with 8 to 11 years of schooling (20.74%). Breast cancer still accounts for the largest cause of death from malignant neoplasms in women. Aspects such as race, education and the composition of Brazilian macro-regions annually impact the increase in the rate of deaths from breast cancer, especially due to the influence of the socioeconomic context, restricting access to health services and qualified medical care, a fact that indicates that social vulnerability is an important obstacle to the achievement of effective health promotion in the country and the control of mortality from malignant breast cancer.